Debonding Time and Dental Pulp Temperature With the Er, Cr: YSGG Laser for Debonding Feldespathic and Lithium Disilicate Veneers - Alikhasi, Marzieh; Monzavi, Abbas; Ebrahimi, Hooman; Pirmoradian-najafabadi, Maryam; Shamshiri, Ahmadreza; Ghazanfari Hashemi, Rezvaneh Sadat (Journal of Lasers in Medical Sciences, 2019)
Introduction: The removal of ceramic veneers is a time-consuming procedure in a dental office. Little research has been done in alternative removal techniques for ceramic veneers. The objective of this study was to evaluate the removal of feldspathic and lithium disilicate reinforced glass ceramic veneers by Er, Cr: YSGG and to measure debonding time and pulpal temperature increase during veneer removal. Methods: Fifty-seven bovine incisor teeth were prepared and divided into 3 groups. Ceramic specimens with a thickness of 0.7mm, a width of 4mm and a length of 8 mm were fabricated from feldspathic ceramic, lithium disilicate reinforced glass ceramic HT (high translucency) and lithium disilicate reinforced glass ceramic MO (medium opacity) (19 for each group). Specimens were cemented on the labial surface of incisors using resin cement. The Er, Cr: YSGG laser was applied to each specimen at 2.5 W and 25 Hz. Debonding time was measured for each specimen, and the intrapulpal temperature was detected in 3 specimens for each group. Data were analyzed via one-way analysis of variance (ANOVA) at significance level of 0.05 (α = 0.05). Results: Mean debonding time was 103.68 (26.76), 106.58 (47.22) and 103.84 (32.90) seconds for feldspathic, lithium disilicate MO, and lithium disilicate HT respectively. There was no significant statistical difference among the groups (P value = 0.96). The intrapulpal temperature increase was less than 1°C in all groups. Conclusion: Er, Cr: YSGG can successfully be used to efficiently debond feldspathic and lithium disilicate reinforced glass ceramic veneers. There was no significant difference for debonding time among these ceramic materials. During ceramic laminate veneer removal by laser irradiation, no irritating temperature rise was detected.